Influencing Factors Of Business-Fraud Intention On Young Muslim Entrepreneurs In Palembang City - Febrianty, Febrianty; Divianto, Divianto (IKONOMIKA, 2019)
ABSTRACT The purpose of this study was to determine the factors that affect the intention of business-fraud on young entrepreneurs in Palembang city. Researchers conducted research development on young-Muslim entrepreneurs as subjects and added the role stress variable and applied TPB Theory. The type of data used in the form of primary data through questionnaires. The analysis of this research used SEM-Analysis. The results of this study were: H1-predicted a positive correlation between attitudes and intention of young-Muslim entrepreneurs to commit business-fraud (accepted). H-2 and H-3 there was rejection because there were more influential variables. H4-predicted there was a positive correlation between the role-stress and intention of young-Muslim entrepreneurs to commit business-fraud (accepted). H5-predicted that attitudes toward behavior, subjective-norms, and perceived-behavioral controls have significant influence on the intention of young Muslim entrepreneurs to commit business-fraud.  Potential business young-Muslim entrepreneurs can fraud occur in the business, needs to be improved by effectiveness of internal controls. Keywords: Intention, Business-Fraud, young-Muslim, attitudes, role-stress, subjective-norms, perceived-behavioral controls, TPB